Pengungkapan Islamic Socal Reporting, ROA, ROE Dan BOPO : Pada Bank Syariah Di Indonesia Tahun 2015-2017 - Perwitasari, Dyah Ayu (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2019)
Disclosure of CSR using the Global Initiative Reporting (GRI) index is limited to material aspects. The GRI measurement is different from measuring CSR disclosure by using the Islamic Social Reporting (ISR) indicator that uses spiritual and social aspects. The purpose of this study is to determine whether Islamic Social Responsibility disclosure has an influence on ROA (Return on Investment), ROE (Return on Equity) and BOPO in Islamic banking in Indonesia in 2015-2017. The sample in this quantitative study is 10 BUSs in Indonesia. The Independent variable in this study uses the Islamic Social Reporting disclosure (ISR) indicator, while the dependent variables are ROA, ROE, and BOPO. The results of the test in this study are Islamic Social reporting has a positive and significant effect on ROA and ROE. While ISR disclosure does not affect BOPO.